Pott’s Puffy Tumor: An Uncommon Clinical Entity - Phillip T. Suwan; Suvarna Mogal; Subhash Chaudhary (Case Reports in Pediatrics)
Although first described in 1760, Pott’s puffy tumor is a lesser known clinical entity. Often seen as a complication of frontal sinusitis, Pott’s is a frontal bone osteomyelitis with an associated subperiosteal abscess. Patients present with a fluctuant swelling of the scalp. The diagnosis is often confirmed with computed tomography (CT). Prompt surgical and medical treatments are the rule as there is the potential for significant morbidity if not quickly diagnosed and treated. Herein, we describe the presentation, diagnosis, and treatment of an 8-year-old female presenting with Pott’s puffy tumor.